(untitled) (Comprehensive Journal of Science, 2026)
Artificial intelligence (AI) is revolutionizing the design and construction field. This study aimed to identify the impact of using AI in building design and implementation. The study employed a descriptive review approach, examining relevant literature. The study’s findings identified a range of opportunities for utilizing AI in the design process, including saving resources, facilitating the creation of plans, generating a large number of creative alternatives, providing design solutions, and enhancing the environmental sustainability of design. Regarding building implementation, AI improves design efficiency by enhancing safety, saving time and effort, reducing errors, predicting potential risks, and improving project and construction site management. However, AI faces a number of challenges in building design and implementation, including: quantitative and qualitative data availability, high initial costs, lack of digital proficiency among workers, weak infrastructure and limited interoperability, and the lack of ethical, regulatory, and legal frameworks.